Chronic ketamine administration impairs mitochondrial complex I in the rat liver - Venâncio, Carlos (2018)
Aim Ketamine can induce hepatotoxicity which has been suggested to be dependent on mitochondrial impairment. This study investigated the long-term effects of chronic low-dose ketamine on liver mitochondrial function, oxidative stress parameters, liver histology and glycogen content. Main methods Adult rats were administered with saline or ketamine (5 or 10 mg/kg) twice a day for a fourteen-day period in order to mimic chronic treatments. Effects between groups were compared ten days after the treatment had ended. Liver mitochondrial function was monitored in isolated mitochondrial extracts through evaluation of respiration parameters and activity of respiratory complexes, as well as oxidative stress, through lipid peroxidation, protein oxidation and superoxide dismutase activity. The hepatic histology and liver glycogen content were also evaluated. Key findings Ketamine groups showed a decreased evolution in body weight gains during the treatment period. Ketamine had no effect either on serum liver enzymes or on the oxidative stress parameters of liver mitochondria. Ketamine decreased the hepatic glycogen content, inhibited mitochondrial complex I and oxygen consumption when glutamate–malate substrate was used. Significance These findings reflect a long-term mitochondrial bioenergetic deterioration induced by ketamine, which may explain the increased susceptibility of some patients to its prolonged or repeated use.